1999
DOI: 10.1177/001440299906500406
|View full text |Cite
|
Sign up to set email alerts
|

Mediation as a Transition Process: The Impact on Postschool Employment Outcomes

Abstract: This article utilizes ethnographic research methods to evaluate the impact of mediation on the transition outcomes of persons with mild mental retardation. The involvement of parents and the focal persons was disproportionate to that of school and agency personnel. School and agency efforts most often resulted in sheltered employment, while personal or parent mediation resulted more often in self-employment and continuing education outcomes. Strategies used by focal persons, their parents, and agencies or scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Family support of youth with disabilities is associated with the achievement of post-school outcomes such as employment, postsecondary education, community living, and engagement in the community (Devlieger & Trach, 1999; Lindstrom, Doren, Metheny, Johnson, & Zane, 2007; Wagner, Newman, Cameto, & Levine, 2005). Additionally, greater levels of family involvement leads to higher reading levels, better grades, and positive school engagement (Newman, 2005).…”
Section: Recommendations For Future Policy and Practicesmentioning
confidence: 99%
“…Family support of youth with disabilities is associated with the achievement of post-school outcomes such as employment, postsecondary education, community living, and engagement in the community (Devlieger & Trach, 1999; Lindstrom, Doren, Metheny, Johnson, & Zane, 2007; Wagner, Newman, Cameto, & Levine, 2005). Additionally, greater levels of family involvement leads to higher reading levels, better grades, and positive school engagement (Newman, 2005).…”
Section: Recommendations For Future Policy and Practicesmentioning
confidence: 99%
“…The purpose of these collaborative activities is to implement an integrated system that addresses the lifelong learning and support needs of a community's members. Devlieger & Trach (1999) found that inter-agency collaboration and support for individual students in transition and their families is an important factor, it facilitates achievement of transition goals, and when done poorly, it limits or impedes those goals.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this collaborative activity is to implement an integrated system that addresses the lifelong learning and support needs of community members. Devlieger & Trach (1999) found collaboration and inter-agency support for pupils in the transition programme was an important factor, facilitating the achievement of a defined transition goal.…”
Section: Collaboration Of Various Agencies In Assisting Transition Prmentioning
confidence: 99%